MATERNITY BENEFITS: OVERLOOKED GENDER RIGHTS IN THE FEMINIZED WORKPLACE OF BANGLADESH’S READY-MADE GARMENT SECTOR - Shill, Shamali; Thambiah, Shanthi; Guna Saigaran, Nithiya (SARJANA, 2025)
ABSTRACT This article explores maternity rights and needs in the women-intensive ready-made garment (RMG) sector in Bangladesh through qualitative research involving 20 female workers, seven factory staff, and three labour rights activists. While some compliant factories follow maternity policies, many violate labour laws regarding employment duration that needs to be fulfilled to be entitled to maternity leave and the value of monetary benefits. Subcontract factories lack maternity provisions, leaving women vulnerable. Even in compliant settings, pregnant workers face health neglect, denial of sick leave, and rejection of options for lighter duties, pressuring some to resign. Mistreatment and forced resignations are common. For those who remain, returning to work eight weeks after childbirth is challenging due to the absence of day-care facilities. These issues heighten stress and hinder the possibility of balancing work and motherhood. The study reveals the exploitation of cheap female labour alongside a disregard for their reproductive roles in this highly feminized RMG industry. It calls for stricter enforcement of existing maternity laws, improved protections, alongside reforms to maternity laws.